Early Brain Injury or Cerebral Vasospasm 2011
DOI: 10.1007/978-3-7091-0356-2_19
|View full text |Cite
|
Sign up to set email alerts
|

Surgical Procedure and Results of Cisternal Washing Therapy for the Prevention of Cerebral Vasospasm Following SAH

Abstract: In 1994, we started cisternal washing therapy (CWT) using urokinase combined with head-shaking method in order to prevent cerebral vasospasm. In this paper, we showed the surgical procedure for CWT and reported the effect of this therapy in preventing vasospasm following SAH. A total of 332 consecutive cases with Fisher group 3 SAH since 1988 were analyzed. Of these patients, 118 cases (56 cases before 1994 and 62 cases after 1994) had not CWT, and, 214 cases after 1994 had this therapy. All of these patients … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 3 publications
0
13
0
1
Order By: Relevance
“…This is in consensus with the retrospective and laboratory study of Riordan et al, 32 who found that mild exercise before the 4th day after aneurysm repair reduced symptomatic vasospasm from 55.2% to 13.6% without promoting neuronal injury. Frequent, systematic mobilization represents a form of kinetic treatment parallel to the "head-shaking method" 30,39 that was meant to help dissolve residual blood clots. The method is often used in conjunction with cisternal and ventricular lavage, 15 and there is strong evidence that it leads to a reduction in vasospasm and improves outcome.…”
Section: Effect Of Early Mobilization and Rehabilitation On Cerebral mentioning
confidence: 99%
See 2 more Smart Citations
“…This is in consensus with the retrospective and laboratory study of Riordan et al, 32 who found that mild exercise before the 4th day after aneurysm repair reduced symptomatic vasospasm from 55.2% to 13.6% without promoting neuronal injury. Frequent, systematic mobilization represents a form of kinetic treatment parallel to the "head-shaking method" 30,39 that was meant to help dissolve residual blood clots. The method is often used in conjunction with cisternal and ventricular lavage, 15 and there is strong evidence that it leads to a reduction in vasospasm and improves outcome.…”
Section: Effect Of Early Mobilization and Rehabilitation On Cerebral mentioning
confidence: 99%
“…The method is often used in conjunction with cisternal and ventricular lavage, 15 and there is strong evidence that it leads to a reduction in vasospasm and improves outcome. 15,22,30,39 Kawamoto et al 22 even concluded that "the effect of head shaking in preventing vasospasm is the most definite compared with any existing treatment protocol. "…”
Section: Effect Of Early Mobilization and Rehabilitation On Cerebral mentioning
confidence: 99%
See 1 more Smart Citation
“…A kinetic therapy using a head shaker or lateral rotational therapy in combination with local thrombolytic therapy has been described [7,136,137]. A recent analysis of three randomized studies, including a combination of thrombolytic and kinetic treatment, revealed a decrease in DCI, CVS and better clinical outcome in two studies [136,137].…”
Section: Kinetic Therapymentioning
confidence: 99%
“…As mentioned before, there is a strong rationale for interventions aimed at the clearance of subarachnoid blood. A kinetic therapy using a head shaker or lateral rotational therapy in combination with local thrombolytic therapy has been described [7,136,137]. A recent analysis of three randomized studies, including a combination of thrombolytic and kinetic treatment, revealed a decrease in DCI, CVS and better clinical outcome in two studies [136,137].…”
Section: Kinetic Therapymentioning
confidence: 99%